Prevalence of Non-specific Chronic Inflammatory Fibromas among Dental Patients Attending Dental OPD Bahawal Victoria Hospital and its Oral Surgery Management - JAVID IQBAL, MUHAMMAD AMJAD BARI, IRSH, MUHAMMAD SAFDAR BAIG (Journal of Fatima Jinnah Medical University, 2018)
Background: It has been observed in routine oral & dental surgery practice the incidence of many soft tissue lesions of the oral cavity which look like a tumor growth. Most of these lesions on surgical excision and afterwards their biopsies are basically indentified as non-specific chronic inflammatory in nature and categorized as the fibrous lesion called fibromas of oral cavity. Some of these lesions are vascular in nature and some pyogenic granulomas while few are giant cell types. Objective: To determine hospital based prevalence of different soft tissues like growth of oral cavity among routine oral and dental surgery patients attending Dental OPD Bahawal Victoria Hospital, Bahawalpur and its oral surgery management. Patients and Methods: This study is based upon the available hospital records of 113 dental minor oral surgery patients presenting with exophytic fibrous lesion like tumors as local irritation fibromas, fibro epithelial oral mucosal hyperplasia, gingival epulis and pyogenic granoloma presenting as non-specific chronic inflammatory fibrous gingival growth. The main variables of interests were the patient’s age, sex, location of the tumor in oral cavity and its surgical management along with patients clinical history and the risk factors identified. Results: Out of 113 patients hospital records 65 (58.05%) were of the fibrous nature (Fibromas), 48 (42.45%) were of bleeding tendencies in nature. Most of the lesions were on the gingival areas 95 (84%) rest of the lesions on the buccal mucoa, palate, tongue and lips. All the lesions were surgically excised and performed electrocautary where needed along with removal of the local irritating cause as well followed with histopathological reports. Conclusion: The role of dental professional for the early detection of such inflammatory lesions in the oral cavity can’t be ignored along with prerequisite knowledge about the clinical history and their presentation in oral cavity for these most frequent lesions. There is need for excisional biopsies for their prevention and control to counter them in the early stage of their development for patient’s better prognosis and to avoid these lesions recurrence.